ANALISIS MINAT BELAJAR MATEMATIKA PESERTA DIDIK KELAS IX SMP NEGERI 15 PADANG - Septi Pratiwi (Jurnal Edukasi dan Penelitian Matematika, 2020)
Learning interest is one of the factors that affect the learning outcomes of students. High learning interest will help students obtain high learning outcomes as well. This research was conducted to determine and analyze the interest in learning mathematics of class IX students of SMP Negeri 15 Padang. The method used in this research is descriptive method with a quantitative approach. The data collection tool in this study was a questionnaire. The results showed that the students' interest in learning mathematics class IX SMP Negeri 15 Padang was in the medium category with an average percentage of  66.52%. Keywords__ Learning Interest, Mathematics Learning, Student